2013
DOI: 10.1053/j.ajkd.2012.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Brain Disease in Hemodialysis Patients: A Cross-sectional Study

Abstract: Background Although dialysis patients are at high risk for stroke and have a high burden of cognitive impairment, there are few reports on anatomic brain findings in the hemodialysis population. Using brain magnetic resonance imaging (MRI), we compared the prevalence of brain abnormalities in hemodialysis patients to a control population without known kidney disease. Study Design Cross-sectional cohort. Setting & Participants 45 maintenance hemodialysis patients and 67 controls without reported kidney dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
102
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 39 publications
3
102
0
2
Order By: Relevance
“…These older patients on hemodialysis are likely at high risk of developing and being diagnosed with dementia and Alzheimer's disease given that they have worse cognitive function than the general population (14,15), have a greater burden of white matter disease and cerebral atrophy (16), experience significant decline in cognitive function while undergoing hemodialysis (17), and have a high burden of cognitive impairment even at younger ages (17)(18)(19). Executive function is the domain of cognition most affected by hemodialysis within the first 2 years after initiation (18), and impairments in executive function are early signs of dementia and Alzheimer's disease (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…These older patients on hemodialysis are likely at high risk of developing and being diagnosed with dementia and Alzheimer's disease given that they have worse cognitive function than the general population (14,15), have a greater burden of white matter disease and cerebral atrophy (16), experience significant decline in cognitive function while undergoing hemodialysis (17), and have a high burden of cognitive impairment even at younger ages (17)(18)(19). Executive function is the domain of cognition most affected by hemodialysis within the first 2 years after initiation (18), and impairments in executive function are early signs of dementia and Alzheimer's disease (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Anatomically, in hemodialysis patients' population more frequent is cerebral atrophy, hippocampal atrophy and silent ischemia (31). Taken that predominantly executive and orientation function are affected; it is indicated that risk factors are the same as in vascular diseases (4).…”
Section: Discussionmentioning
confidence: 99%
“…The study by Drew et al (9) found significantly greater degrees of cerebral and hippocampal atrophy, typical findings in Alzheimer's disease, as well as greater numbers of infarcts in the hemodialysis patients compared with controls.…”
mentioning
confidence: 94%
“…Drew et al (9) also recently reported results of brain magnetic resonance imaging (MRI) in 45 hemodialysis patients compared with 67 controls in a younger subsample (mean555 years) of the same population (9). The study by Drew et al (9) found significantly greater degrees of cerebral and hippocampal atrophy, typical findings in Alzheimer's disease, as well as greater numbers of infarcts in the hemodialysis patients compared with controls.…”
mentioning
confidence: 99%